Modernitas dan Dislokasi Budaya: Studi tentang Hilangnya Praktik Kearifan Lokal pada Masyarakat Asmat - Sarang, Rikardus Kristian; Jiaripits, Abel (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2025)
This article analyzes the impact of modernity on cultural dislocation in Asmat society, focusing on the loss of local wisdom practices that have long been central to their cultural identity. This research uses two main techniques, namely in-depth interviews and Focus Group Discussions (FGDs), to explore the Asmat people's perspectives on the social and cultural changes they are experiencing. The findings show that modernity, triggered by globalization, technological development, and information flow, has caused a shift in traditional values, changed life patterns, and threatened the preservation of local wisdom. This cultural dislocation not only impacts on social aspects, but also on Asmat cultural identity and sustainability. This research provides insights into the challenges communities face in maintaining their traditions amidst modernity, and offers strategic recommendations to safeguard an almost forgotten cultural heritage. The findings are expected to make an important contribution to the development of cultural studies and the preservation of local wisdom.